2022
DOI: 10.1298/ptr.e10201
|View full text |Cite
|
Sign up to set email alerts
|

Pain in Spinal Muscular Atrophy: A Questionnaire Study

Abstract: This study aimed to reveal the chronic pain prevalence in spinal muscular atrophy (SMA) patients and identify the clinical characteristics of these patients with chronic pain. The pain status was also investigated in SMA patients with chronic pain. Methods: This cross-sectional study was conducted between July 2018 and December 2018. SMA type II and type III patients in Japan were mailed a survey questionnaire. The survey items were chronic pain prevalence, clinical characteristics, and motor function. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Pitarch-Castellano et al 34 , Sagerer et al 35 , and Uchio et al 36 described the occurrence of pain in SMA patients. They found a prevalence of pain in 27% to approximately 40% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Pitarch-Castellano et al 34 , Sagerer et al 35 , and Uchio et al 36 described the occurrence of pain in SMA patients. They found a prevalence of pain in 27% to approximately 40% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Only one of the aforementioned studies [15][16][17][18][19]34] reported results in a pediatric SMA population. The results of Lager et al's study on 17 teenagers with SMA highlighted that pain is a frequent problem in adolescents, with 69% of the population reporting pain within the last three months and 50% reporting chronic pain [34].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study showed that 55% of adult SMA type III walker patients in their sample presented nociceptive pain, as measured with different tools (pressure algometer, myotonometry), hypothesizing that it is caused by changes in the imbalanced musculoskeletal system due to muscle weakness [18]. Finally, another recent study in SMA patients, both children and type II and type III adults, using a questionnaire of in-house design, showed chronic, frequent, and low-intensity pain among the SMA population [19]. Therefore, well-designed patient and caregiver-oriented outcome measures are still needed to ensure that we are measuring the most relevant and clinically meaningful outcomes [20].…”
Section: Introductionmentioning
confidence: 96%
“…Only three studies so far have investigated pain in patients with SMA where children and adolescents were part of the study population. It was shown that the prevalence of chronic pain in type 2 (mean age 17.3 ± 11.7 years) and type 3 SMA patients (mean age 44.9 ± 21.6 years) was 40.6% and 40.9%, respectively [11]. Pain intensity in SMA patients was mild, but pain usually occurred daily, for prolonged durations, and most often in the neck, back, and lower extremities.…”
Section: Introductionmentioning
confidence: 98%
“…Pain intensity in SMA patients was mild, but pain usually occurred daily, for prolonged durations, and most often in the neck, back, and lower extremities. Sitting and high physical activity exacerbated pain the most [11].…”
Section: Introductionmentioning
confidence: 99%